An exploratory review of legal texts and literature on living tenure systems in Madagascar - McLain, R.; Ranjatson, P.; Heidenrich, T.; Rakotonirina, J.M.; Nomenjanahary, A.R.F.; Razafimbelo, N.T.R. (Center for International Forestry Research, 2021)
A lack of information about the living customary systems that manage commons in Madagascar hampers efforts to identify the levels at which collectivities charged with allocating land and enforcing land claims should receive legal recognition. To help address this knowledge gap and inform ongoing legal reforms aimed at recognizing collective tenure, we reviewed relevant legal texts and field studies of Malagasy tenure systems. Our review of legal texts revealed that the lack of a clear legal definition of the collectivities located closest to rural villagers is a major obstacle to efforts aimed at recognizing the land allocation and governance rights of existing local institutions. At the same time, our review of field research of customary tenure systems demonstrates that these systems continue to function more or less effectively in many parts of rural Madagascar. The evidence also suggests that the positive effect of customary tenure systems on conservation outcomes is contingent upon the degree to which those making and enforcing the rules are perceived to have legitimacy, as well as the degree to which the rules reflect local realities and values. This argues in favour of providing clear statutory recognition of local-level customary institutions, and their authority to establish and regulate use of land and forests.